Analysis of Modulation Translation Techniques in the Film Subtitles of "Under Paris" - Aulia Ramadina; Farida Amalia; Dudung Gumilar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to describe the forms of modulation translation techniques applied in the subtitles of the film Under Paris and analyze the effect of their application on the shift in meaning between French as the source language and Indonesian as the target language. This study focuses on modulation techniques based on the theoretical framework of Vinay and Darbelnet and the adjustment of meaning based on the theory of Nida and Taber. The method used is descriptive qualitative with data sources in the form of dialogue in the subtitles of the film Under Paris (2024). Data were collected through listening and note-taking techniques, then analyzed interpretively. The results of the study are that all seven forms of modulation techniques according to Vinay and Darbelnet were found in the data, namely abstract-concrete shifts, cause-effect, whole-part, positive-negative, active-passive, physical-psychological, and space-time. Of the total data analyzed, 40 data were found containing modulation techniques, with positive-negative modulation as the most dominant form. In addition, the application of modulation techniques shows a close relationship with the adjustment of meaning as stated by Nida and Taber. Although not all semantic adjustment categories appear in every modulation data, context-based adjustments are the most frequently used category, indicating the importance of situational and visual context in subtitle translation. The study concludes that modulation techniques play a significant role in producing subtitle translations that are natural, acceptable, and appropriate to the audiovisual context.